2008
DOI: 10.1111/j.1600-0420.2007.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotype and risk for development of cataract and age‐related macular degeneration

Abstract: ABSTRACT.Purpose: To study whether apolipoprotein E (APOE) genotypes are associated with risk for developing cataract and age-related macular degeneration (AMD).Methods: A sample of 88 healthy adults (50-75 years) genotyped for polymorphisms of APOE underwent an eye examination which included visual acuity (VA) testing, slitlamp cataract evaluation, optical coherence tomography (OCT) and fundus photography, the last of which was analysed and graded for macular pathology at the Reading Centre, Moorfields Eye Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…We could not detect statistically significant association in our population between other minor susceptibility genes and advanced AMD, such as CST3, CX3CR1, FBLN5, HMCN1, PON1, SOD2, TLR4, VEGFA and VLDLR, in agreement with other reports (Schultz et al 2003; Abecasis et al 2004; Baird et al 2004; Hayashi et al 2004; Bojanowski et al 2005; Esfandiary et al 2005; Schmidt et al 2005; Fuse et al 2006; Kaur et al 2006; Seitsonen et al 2006; Fisher et al 2007; Richardson et al 2007; Despriet et al 2008; Edwards et al 2008; Utheim et al 2008). Discrepancies in replication of risk variants in association studies could be caused by population heterogeneity, disease heterogeneity, and/or the use of different diagnostic criteria among cases, but it could also reflect the lack of power to detect modest gene effects with undersized samples.…”
Section: Discussionsupporting
confidence: 92%
“…We could not detect statistically significant association in our population between other minor susceptibility genes and advanced AMD, such as CST3, CX3CR1, FBLN5, HMCN1, PON1, SOD2, TLR4, VEGFA and VLDLR, in agreement with other reports (Schultz et al 2003; Abecasis et al 2004; Baird et al 2004; Hayashi et al 2004; Bojanowski et al 2005; Esfandiary et al 2005; Schmidt et al 2005; Fuse et al 2006; Kaur et al 2006; Seitsonen et al 2006; Fisher et al 2007; Richardson et al 2007; Despriet et al 2008; Edwards et al 2008; Utheim et al 2008). Discrepancies in replication of risk variants in association studies could be caused by population heterogeneity, disease heterogeneity, and/or the use of different diagnostic criteria among cases, but it could also reflect the lack of power to detect modest gene effects with undersized samples.…”
Section: Discussionsupporting
confidence: 92%
“…Lipid levels including HDL cholesterol were evaluated in serum and APOE genotyping was performed as previously described (Ancelin et al, 2010), ε4 allele having been found to be protective of ocular diseases (Baird et al, 2004;Utheim et al, 2008).…”
Section: Socio-demographic and Clinical Variablesmentioning
confidence: 99%
“…These results have been replicated in other studies [112,113,114,115,116,117,118,119,120,121,122] and confirmed by a meta-analysis [123]. However, likely because of the weak allele effects of Apo-ε, and because of the low allele frequencies of both the ε2 and ε4 alleles, some studies could not demonstrate any association between this gene and AMD [124,125,126,127,128,129]. The ε4 allele is associated with a reduced risk of developing different subtypes of the disease (exudative or atrophic forms) [115,116], with sometimes a gender-specific protective effect reported for men [117], whereas a gender effect of the ε2 isoform might confer an increased risk mainly for men [115].…”
Section: Genetic Factors Associated With Amdmentioning
confidence: 60%